Judicial Reform in Afghanistan: Towards a Holistic Understanding of Legitimacy in Post-Conflict Societies - Christensen, Maren I. (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: This investigation seeks to elucidate the connections among three aspects of rule of law through an examination of judicial reform in post-Taliban Afghanistan. I hypothesize that building judicial independence, engagement with customary law, and anti-corruption efforts, usually approached separately, are interdependent through their impacts on legitimacy. Failings in post-2001 Afghanistan, particularly the insistence on building rule of law from the top-down, have resulted in a formal judiciary that is neither independent, nor accountable, nor culturally viable. Taking note of the way in which these failings are being harnessed by the insurgency to further divide the nation as a whole and prevent the state from building legitimacy, the theoretical hypothesis is supported: effectiveness and appeal to tradition are necessary conditions for building legitimacy. These conditions are satisfied, respectively, through (1) successful anti-corruption and independent, sustainable institution building, and (2) consultation and genuine engagement with all sources of traditional authority. Having come to an understanding of the importance of bottom-up and top-down rule of law, I recommend that while we sustain our efforts in anti-corruption and institution building in the formal sector, we also need direct engagement that is community-specific: bringing together traditional leaders, local state justice officials, and progressive stakeholders such as women's rights advocates to come to a better understanding of each other's intentions, priorities, practices and values. This kind of dialogue would build non-coercive consensus on an arrangement that covers all bases in the administration of justice between the courts and informal jirgas or shuras. Once a number of these groups have been successful, there will be stronger impetus to replicate this dialogue at the national level, bridging top-down institution building and legal development with bottom-up social transformation. Such a holistic approach would garner state legitimacy in a way that is simultaneously modern, effective, and genuinely Afghan.